Anatomic Measurement and Variability Analysis of the Anterior Talofibular Ligament and Calcaneofibular Ligament of the Ankle. Issue 11 (8th November 2021) - Yang, Han; Su, Minghao; Chen, Zhimin; Qu, Rongmei; Yuan, Zhirong; Yuan, Jiajie; He, Shanli; Li, Zeyu; Liu, Chang; Xiao, Zhaoming; Liang, Haibin; Ouyang, Jun; et al.
Background: The anterior talofibular ligament (ATFL) and calcaneofibular ligament (CFL) contribute greatly to the overall stability of the ankle joint; however, ATFL and combined ATFL-CFL sprains are common. Anatomic reconstruction of the lateral collateral ligament with grafts has been proposed for patients with poor tissue quality or inadequate local tissue. Anatomic reconstruction of the lateral ankle ligaments requires a good understanding of their anatomic location. Purpose: To describe the anatomy of the ATFL and CFL ligaments quantitatively and qualitatively and explore the relationship of some morphological parameters. Study Design: Descriptive laboratory study. Methods: A total of 66 adult ankle specimens were analyzed for ATFL band type, origin, length, width, thickness, and angle between the ATFL and CFL, and 73 adult ankle specimens were used for measuring the origin of the CFL. The coefficient of variation was used to describe and compare the respective variability of angle, length, width, and thickness. The origin of the ATFL was labeled as point A, and the leading edge of the CFL intersection with the articular surface of the calcaneus was considered point B . Results: The ATFL had a variable number of bands. A high degree of variability (coefficient of variation >0.2) was seen for most morphological measurements of the ATFL. In addition, the length of distance AB also varied. The CFL originated at the tip of the fibula in only 9% of specimens. It was found more commonly at the anterior border of the lateral malleolus (4.94 ± 1.70 mm from the tip). The angle between the ATFL and CFL was consistent at 100° to 105º. Conclusion: A fair amount of variability of ATFL length, width, and thickness were found in our study, with less variability in the ATFL-CFL angle. Most CFLs attached anterior to the tip of the fibula. Clinical Relevance: Providing relevant anatomic data of ATFL and CFL is important in ensuring proper surgical treatment of ankle joint injuries.